2000
DOI: 10.1042/bst0280578
|View full text |Cite
|
Sign up to set email alerts
|

Litchi chinensis fatty acid diversity: occurrence of the unusual cyclopropanoic fatty acids

Abstract: Litchi chinensis (Sapindaceae) is a tree that originates from China and is cultivated for its sweet fruits all over the world in warm climates. Unusual fatty acids such as cyclopropanoic fatty acids have been identified in the seeds of Litchi. Because of their potential value for industry (as inks, cosmetics, detergents, lubricants, etc.), the variability in the relative levels of unusual fatty acids in the seeds of 28 different Litchi varieties was analysed at two locations (on Réunion Island in the Indian Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…is a subtropical and tropical fruit with high commercial value. The fruit has a white, translucent, sweet and juicy aril, which is surrounded by a bright red skin (Gontier et al. 2000; Jiang et al.…”
Section: Introductionmentioning
confidence: 99%
“…is a subtropical and tropical fruit with high commercial value. The fruit has a white, translucent, sweet and juicy aril, which is surrounded by a bright red skin (Gontier et al. 2000; Jiang et al.…”
Section: Introductionmentioning
confidence: 99%
“…These factors should be considered and serve as point of comparison depending on the study or innovation that will be made referring to the study sample, seeking to obtain better results. It has been found that most of the samples contain FA such as linoleic, oleic, palmitic and stearic (Zhang et al, 2016;Yang et al, 2016;Vieira et al, 2016;Salvador et al, 2016;Moser et al, 2016;Ling et al, 2016;Krulj et al, 2016;Domingues et al, 2016;Bozdogan and Mungan, 2016;Shan-Sahn et al, 2015;Santos et al, 2013;Botinestean et al, 2012;Neuza et al, 2011;Szentmihalyi et al, 2002;Gontier et al, 2000;Gaydou et al, 1993), in addition to these being found in higher concentration and presenting several positive effects on health (Simopoulos, 2008).…”
Section: Recent Researchmentioning
confidence: 99%
“…Other adjuvant strategies to prolong the survival rate of NSCLC patients administered TKIs should be developed [24]. Litchi ( Litchi chinensis , Sapindaceae) is a warm-climate fruit tree that originates from southern China and is cultivated in semi-tropical areas of the world for its delicious fruit [5]. In traditional Chinese herbal medicine, the function of litchi seeds are the release of stagnant humor and remote chilling, and they are used as analgesic agent capable of relieving cough, gastralgia, neuralgia, orchitis, colic, testicular swelling and smallpox [6].…”
Section: Introductionmentioning
confidence: 99%